15.2k views
5 votes
Hi!! ;; please help :) 20 points! no links or websites. please .

Hi!! ;; please help :) 20 points! no links or websites. please .-example-1
User Raugfer
by
5.5k points

1 Answer

5 votes

Answer: 22

Explanation:

(1 × 3) + [2 × 3
(1)/(2)] + [1 × 3
(3)/(4) [1 × 4
(1)/(4)] + [3 ×
(3)/(4)] + [3 × 5
(1)/(4)]

= 3 + [2 ×
(3)/(2)] + [1 ×
(9)/(4)] + [1 ×
(4)/(4)] + [3 ×
(12)/(4)] + [3 ×
(5)/(4)]

= 3 +
(6)/(2) +
(9)/(4) +
(4)/(4) (equal to 1) +
(36)/(4) +
(15)/(4)

= 3 + 3 +
(9)/(4) + 1 + 9 +
(15)/(4)

= 16 +
(9+15)/(4)

= 16 +
(24)/(4)

= 16 + 6

= 22

User AndrewWinn
by
5.3k points